STRATEGI PENGEMBANGAN EKOWISATA MANGROVE DI DESA NISOMBALIA KABUPATEN MAROS SULAWESI SELATAN - Andi Akram; Muh Ridha; Ahmad Fauzan; Rezki Ramadhan; Randi (Techno-Fish, 2023)
This study aims to analyze the potential of mangrove resources in Nisombalia village, analyze damage to mangrove forests and formulate strategies for developing mangrove ecotourism in Nisombalia village. The method used in this research is analysis of the level of damage based on direct surveys of mangrove conditions, interpretation of Landsat 8 imagery, interviews, filling out questionnaires for economic valuation of mangroves and SWOT analysis for determining the direction of mangrove ecotourism development strategies. The results obtained for mangrove conditions for the type of Rhizopora apiculate showed the highest percentage of coverage of 57.81%. The results of image interpretation also show that there has been a reduction and increase in area from 2018-2022 and for the total economic value in Nisombalia Village of Rp. 35,442,557,718. There are 2 strategic directions for the rehabilitation of mangrove ecosystems which are the top priority in Nisombalia Village, namely: 1) Restoring the function of mangrove forests according to the rehabilitation ecological space pattern; 2) Provision of mangrove cultivation facilities (nursery and seeding) which are managed directly by the community.